2014
DOI: 10.1182/blood-2013-11-538835
|View full text |Cite|
|
Sign up to set email alerts
|

Pomalidomide alone or in combination with low-dose dexamethasone in relapsed and refractory multiple myeloma: a randomized phase 2 study

Abstract: • Pomalidomide plus lowdose dexamethasone significantly improved PFS vs pomalidomide alone in relapsed and refractory multiple myeloma.• Pomalidomide plus low-dose dexamethasone is an important new treatment option for RRMM patients who have received multiple prior therapies.This multicenter, open-label, randomized phase 2 study assessed the efficacy and safety of pomalidomide (POM) with/without low-dose dexamethasone (LoDEX) in patients with relapsed/refractory multiple myeloma (RRMM). Patients who had receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
300
2
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 349 publications
(342 citation statements)
references
References 40 publications
28
300
2
12
Order By: Relevance
“…Although pomalidomide has not been evaluated in the setting of consolidation after autologous HSCT, a 2% to 4% rate of VTE with thromboprophylaxis has been reported in the setting of relapsed/ refractory myeloma. [56][57][58] Thromboprophylaxis strategies have not been specifically evaluated in patients on maintenance therapy with novel immune-modulatory agents after transplant, however, studies in patients with newly diagnosed MM receiving lenalidomide or thalidomide-based treatments show a significant benefit of thromboprophylaxis. 59,60 Palumbo et al 59 randomly assigned 659 patients receiving thalidomide-based regimens to low-dose aspirin, warfarin or enoxaparin.…”
Section: Multiple Myelomamentioning
confidence: 99%
“…Although pomalidomide has not been evaluated in the setting of consolidation after autologous HSCT, a 2% to 4% rate of VTE with thromboprophylaxis has been reported in the setting of relapsed/ refractory myeloma. [56][57][58] Thromboprophylaxis strategies have not been specifically evaluated in patients on maintenance therapy with novel immune-modulatory agents after transplant, however, studies in patients with newly diagnosed MM receiving lenalidomide or thalidomide-based treatments show a significant benefit of thromboprophylaxis. 59,60 Palumbo et al 59 randomly assigned 659 patients receiving thalidomide-based regimens to low-dose aspirin, warfarin or enoxaparin.…”
Section: Multiple Myelomamentioning
confidence: 99%
“…12 A phase 3 study of pomalidomide plus low-dose dexamethasone vs high-dose dexamethasone alone demonstrated a significant benefit to OS, PFS, and overall response rate (ORR). 13 Notably, subgroup analyses demonstrated a benefit to OS and PFS in lenalidomide-refractory patients treated with pomalidomide plus low-dose dexamethasone vs high-dose dexamethasone.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that pomalidomide + low-dose dexamethasone should be considered a standard of care in patients with refractory or relapsed and refractory multiple myeloma regardless of prior treatment. Philippe Moreau, 7 Anne Banos, 8 Albert Oriol, 9 Laurent Garderet, 10 Michele Cavo, 11 Valentina Ivanova, 12 Adrian Alegre, 13 Joaquin Martinez-Lopez, 14 Christine Chen, 15 Christoph Renner, 16 Nizar Jacques Bahlis, 17 Xin Yu, 18 Terri Teasdale, the management of patients who have exhausted treatment with BORT, LEN, and THAL. In the treatment of RRMM, the decision whether to switch agent classes (i.e.…”
Section: Introductionmentioning
confidence: 99%